Implementation of the Independent Curriculum in Islamic Religion Subjects - Fachri Husaini Hasibuan; Salminawati Salminawati; Sapri Sapri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to explain how the Merdeka Curriculum is implemented in Islamic Religious Education subjects at Harapan Mandiri Middle School in Medan. The research method is qualitative using a critical discourse analysis approach, namely observing facts that actually occurred and comparing them with related documents and testing the level of achievement. The research results obtained are, firstly, the Merdeka curriculum at Harapan Mandiri Middle School in Medan includes three activities, namely diagnostic assessment, P5 (Pancasila Student Profile Strengthening Project), and PMO (Project Management Office). Both PAI teaching processes with the Independent Curriculum at Harapan Mandiri Middle School in Medan have fully adopted the Independent Curriculum approach in planning, implementation and assessment. The three student learning outcomes when the Merdeka Curriculum was applied to Islamic Religion subjects at Harapan Mandiri Middle School in Medan showed a significant increase in the cognitive and psychomotor aspects, but the affective aspect experienced a less significant increase. The four obstacles in implementing the Merdeka Curriculum in Islamic Religion subjects at Harapan Mandiri Middle School in Medan involve senior teachers who are less familiar with technology as an internal problem, and parents who do not understand the Merdeka Curriculum as an external problem. The recommended solution to overcome obstacles in implementing the Merdeka Curriculum at Harapan Mandiri Middle School in Medan is that teachers must improve their pedagogical competence by reading educational books, writing scientific papers, following the latest news, and taking part in training. Parents of students who do not understand the Merdeka Curriculum are advised to can communicate effectively and provide regular explanations regarding the independent curriculum.